Apples: Botany, Production and Uses 2003
DOI: 10.1079/9780851995922.0409
|View full text |Cite
|
Sign up to set email alerts
|

Flower and fruit thinning and vegetative: fruiting balance.

Abstract: The history of flower and fruit thinning, along with the commercially important physiological effects of thinning are discussed. Adjuvants and thinning chemicals and their physiological effects, as well as their applications are presented. The influence of photosynthetic reserves on the fruit set and chemical thinning of apples following ovule fertilization are also discussed. Notes are presented on chemicals that induce flower bud formation without thinning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 0 publications
2
51
1
Order By: Relevance
“…Previous studies on apples have also found a decrease in vegetative growth as crop load increases, an effect which extended even into subsequent growing seasons (Byers, 2003;Embree et al, 2007;Wright et al, 2006). However, in our work, 'Caricia' shoots were never shorter than those of 'Eva', even under the highest crop load treatments (Figure 1).…”
Section: Discussioncontrasting
confidence: 51%
“…Previous studies on apples have also found a decrease in vegetative growth as crop load increases, an effect which extended even into subsequent growing seasons (Byers, 2003;Embree et al, 2007;Wright et al, 2006). However, in our work, 'Caricia' shoots were never shorter than those of 'Eva', even under the highest crop load treatments (Figure 1).…”
Section: Discussioncontrasting
confidence: 51%
“…Fruit quality and consumer acceptance of fresh market peaches is largely defined by fruit size, flavour, melting texture, and surface and flesh color [2,3]. For producers, fruit size is the primary factor affecting yield and crop value.…”
Section: Introductionmentioning
confidence: 99%
“…Removing fruitlets by hand thinning is typically performed at stage II of fruit development (pit hardening), 40 -60 days after full bloom (DAFB) [2,3,5]. In Canada, hand thinning can require between 100 -150 h·ha -1 depending on tree vigour, age, size, and fruit set, resulting in a estimated cost of ~$1235 ha -1 per year [6] based on current wages and benefits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Managing crop load in apple orchards is essential for improving fruit size and color, preventing broken limbs due to the excess weight of fruit, and ensuring adequate return bloom to minimize biennial bearing (Byers, 2003;Dennis, 2000). Thinning, or reducing the number of apples per tree and within each fruiting cluster, can also decrease disease pressure by allowing for more rapid drying conditions within fruit clusters and allowing for more complete spray coverage of the developing fruitlets.…”
mentioning
confidence: 99%